Numeral simulation of droplet evaporation-atomization under hot air flow - Chao Lv; Lu-Lu Zhang; Ning Wei; Xu-Xin Chen; Hong-Liang Zhao; Wei-Guang Hao (Case Studies in Thermal Engineering)
In the field of cerium oxide preparation by spray pyrolysis, understanding the droplet atomization-evaporation process is an innovative and promising concept. The spray pyrolysis process offers significant advantages over conventional methods, promoting energy efficiency and environmental sustainability by eliminating wastewater and exhaust gas emissions. Optimizing energy utilization to meet increasing demands is a critical focus. Moreover, the impact of hot air flow on droplets directly influences product morphology, thereby enhancing the high-value application of cerium oxide. Using FLUENT software, this study established a single droplet evaporation model and a coupling model for droplet atomization-evaporation during secondary atomization. The research explored the evaporation mechanism and microscopic changes occurring during droplet atomization. The research results indicate that increasing the ambient temperature, enhancing convective intensity, and changing the diameter accelerate the evaporation rate of the droplet, lead to more complete droplet fragmentation, and shorten both the evaporation lifetime and duration. The deformation process of the droplet in the hot airflow is not instantaneous, but rather a continuous energy transfer process. A distinct groove forms around the parent droplet and persists throughout the entire process. Additionally, investigating hot gas flow fragmentation positively impacts the efficient combustion of engine fuel.